2010
DOI: 10.1074/jbc.m110.104547
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Substrate-binding Site in a Peroxisomal β-Oxidation Enzyme by Photoaffinity Labeling with a Novel Palmitoyl Derivative

Abstract: Peroxisomes play an essential role in a number of important metabolic pathways including ␤-oxidation of fatty acids and their derivatives. Therefore, peroxisomes possess various ␤-oxidation enzymes and specialized fatty acid transport systems. However, the molecular mechanisms of these proteins, especially in terms of substrate binding, are still unknown. In this study, to identify the substrate-binding sites of these proteins, we synthesized a photoreactive palmitic acid analogue bearing a diazirine moiety as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Kashiwayama et al [36] found that the area Trp249-Arg251 is essential for substrate binding and W249G variation leaves the capacity of the enzyme to bind substrates to a level of 30% of the native protein, a feature seen also in our results by increasing K m . In the yeast complementation experiment, both R248C and W249G enzymes could still utilize LCFAs (Figure 2).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Kashiwayama et al [36] found that the area Trp249-Arg251 is essential for substrate binding and W249G variation leaves the capacity of the enzyme to bind substrates to a level of 30% of the native protein, a feature seen also in our results by increasing K m . In the yeast complementation experiment, both R248C and W249G enzymes could still utilize LCFAs (Figure 2).…”
Section: Resultssupporting
confidence: 76%
“…This could loosen the structure locally, which is supported by the increased temperature sensitivity (Table 1), and disturb the binding of NAD + , seen in the activity measurements as a need for a large surplus of NAD + to achieve measurable data. In MD simulations the fluctuation extends also to the signature Ser-Tyr-Lys catalytic triad of the SDR superfamily [35], as well as to the cavity area (Figure 4) important for the substrate binding [36]. Most important seems to be, however, that the hydrogen bond not involving any side chain atoms (T15 N to V97 O ) seems to be more stable.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The uptake of BSA-or RBPassociated [ 14 C] DHA (14 nM) by the capped cRNA-or waterinjected Xenopus laevis oocytes was examined as reported previously. 25) The uptake amount of [ 14 C] DHA in the oocytes was evaluated as the oocyte-to-medium (oocyte/medium) ratio (µL/oocyte) as reported previously. 25) Chemical Synthesis of Photoreactive DHA Analogue Bearing a Diazirine Moiety as a Photophore (Fig.…”
Section: Methodsmentioning
confidence: 99%